Membangun Budaya Kreatif Melalui Seni Batik di Yayasan Cinta Yatim & Dhuafa, Pisangan Barat, Kec.Cirendeu, Kota Tangerang Selatan - Susan Ary Ayu Anjani; Shela Amelia AKhap; Muhammad Farhan Nugraha; Muammar Khadafi; Ahmad Fajar Mahendra; Dian Islami; Adriansyah Harun; Rochman Rayhan; Reza Setiansa; Sa’diah El Adawiyah (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Abstract. Education plays an important role in shaping a bright and sustainable future, with creative and fun learning as the key to creating an inspiring learning environment. This article examines the event "SEBATIK - Batik Art for Creative Culture" held at the Yayasan Cinta Yatim dan Dhuafa, Cirendeu, South Tangerang on July 20, 2024. This event aims to introduce and preserve batik art, as well as to arouse interest and appreciation for traditional arts among the children of the foundation. With a creative and interactive approach, this workshop teaches basic batik techniques through training and direct practice, and provides appreciation to participants through prizes. The evaluation results show that this activity has succeeded in increasing the creativity and skills of children, as well as strengthening the relationship between the foundation and the community. This workshop also has the potential to open up new business opportunities for foster children, increasing their economic independence in the future. This article presents details of the event implementation, the results achieved, and its impact on participants and the foundation.